2023
DOI: 10.1108/tqm-08-2022-0266
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing small and medium-sized enterprise (SME) resilience during the COVID-19 outbreak

Abstract: PurposeThis research paper highlights the economic impact on small and medium-sized enterprises (SMEs) due to Coronavirus outbreaks. It proposes factors that influence the strengthening and survival of SMEs.Design/methodology/approachIn this research, resilience is reflected in the following aspects hope, problem resolution and persistence. This quantitative study analyses a purposive sample of 120 small and medium-sized firms in India. The study's primary data are the responses to questionnaires issued to res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 88 publications
0
3
0
Order By: Relevance
“…Other factors influencing the ability of SMEs to survive and cope with the coronacrisis include employee and customer satisfaction in the changing situations. (Khan et al 2022;Fasth et al 2022;Thekkoote 2023). A study by Dyduch et al (2021) showed that the alignment of the organisation's internal and external environments had a mitigating effect on the decline in business performance during the coronacrisis.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Other factors influencing the ability of SMEs to survive and cope with the coronacrisis include employee and customer satisfaction in the changing situations. (Khan et al 2022;Fasth et al 2022;Thekkoote 2023). A study by Dyduch et al (2021) showed that the alignment of the organisation's internal and external environments had a mitigating effect on the decline in business performance during the coronacrisis.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Small-scale businesses are at risk of failure when their sales revenue declines due to thin profit margins, lack of financial reserves (if any), and limited access to debt financing [11]. It should be noted that the pandemic's impact is not uniform across all MSMEs and depends on various factors, such as industry sector, business size, business model, consumer behavior dynamics, and government interventions [12,13]. For example, this study found that traditional herbal beverage businesses did not experience negative effects and, in fact, benefited from the COVID-19 crisis.…”
Section: The Impact Of the Covid-19 Pandemic And Business Sustainabil...mentioning
confidence: 99%
“…Scholarly journals have widely discussed models of entrepreneurial marketing versus resilience theory for small businesses. Most of the emphasis touches on the importance of EM for small business resilience, such as the factor analysis of SME resilience amid COVID-19 [72]; effectual causal logic for small firms' resilience, such as organizational learning, firm resources, and organization plan-oriented strategy during the pandemic [73][74][75][76][77]; and the design framework for dynamic organizational strength [78,79]. All of these offered groundbreaking novelties in navigating the practical application for MSME's sustainable market and firm's innovation, technology adoption, and stakeholder relations strategies, to name the least.…”
Section: Model Of Entrepreneurial Marketing Behavior Post the Disastermentioning
confidence: 99%